Strategies to mitigate drudgeries of women in agriculture - Ponnusamy, K.; Nayak, Jyoti; Adhiguru, P. (Indian Farming, 2016)
Farm women invariably experience drudgery in both household chores and various farm operations. Strenuous efforts are required to address the different kinds of drudgeries of farm women. Appropriate extension strategies designed to suit the working needs of farm women can help to increase the efficiency. This will also facilitate timely completion of farm operations and increase the probability of higher returns.